Review of Thin Film Nanocomposite Membranes and Their Applications in Desalination - Nambi Krishnan, Jegatha; Venkatachalam, Kaarthick Raaja; Ghosh, Oindrila; Jhaveri, Krutarth; Palakodeti, Advait; Nair, Nikhil (Frontiers in Chemistry, 2022)
All over the world, almost one billion people live in regions where water is scarce. It is also estimated that by 2035, almost 3.5 billion people will be experiencing water scarcity. Hence, there is a need for water based technologies. In separation processes, membrane based technologies have been a popular choice due to its advantages over other techniques. In recent decades, sustained research in the field of membrane technology has seen a remarkable surge in the development of membrane technology, particularly because of reduction of energy footprints and cost. One such development is the inclusion of nanoparticles in thin film composite (TFC) membranes, commonly referred to as Thin Film Nanocomposite Membranes (TFN). This review covers the development, characteristics, advantages, and applications of TFN technology since its introduction in 2007 by Hoek. After a brief overview on the existing membrane technology, this review discusses TFN membranes. This discussion includes TFN membrane synthesis, characterization, and enhanced properties due to the incorporation of nanoparticles. An attempt is made to summarize the various nanoparticles used for preparing TFNs and the effects they have on membrane performance towards desalination. The improvement in membrane performance is generally observed in properties such as permeability, selectivity, chlorine stability, and antifouling. Subsequently, the application of TFNs in Reverse Osmosis (RO) alongside other desalination alternatives like Multiple Effect Flash (MEF) evaporator and Multi-Stage Flash (MSF) distillation is covered.